IMPACT OF AQUACULTURE AS A DEVELOPMENTAL ACTIVITY FOR WOMEN SELF-HELP GROUPS IN GANJAM DISTRICT OF ORISSA - PANDA, NIRUPAMA; SAHOO, L. N.; RATH, D. P. (Journal of the Inland Fisheries Society of India, 2021)
Aquaculture activity has positive impact on the socio-economic condition as well as empowerment of the members of women self-help groups (WSHGs) with significant increase in development indicators. By undertaking aquaculture activity, the WSHGs have succeeded in production of fish, employment generation and contributing to expenditure on food.The number of WSHGs in both high level and high middle level categories were about 2.5 times that of those in low middle and the low level categories in economic, social and empowerment sectors and more than 1.5 times higher in case of overall development. Multiple regression model revealed that training has the highest effect in estimating the financial contribution (t =27.5) where as the size of the group had negative effect (r=-182.6). All other three variables viz. group savings, bank loan and profit contributed positively to financial contribution of the members to their families. Key words: Aquaculture, women self-help groups, Orissa, social empowerment, socio-economic indicators